Morphology and molecular phylogeny of Hyalosynedra lanceolata sp. nov. and an extended description of Hyalosynedra (Bacillariophyta). Issue 2 (3rd April 2018) - Belando, Ma Dolores; Jiménez, Juan F.; Marín, Arnaldo; Aboal, Marina
ABSTRACT: The araphid diatom genus Hyalosynedra is a very common component of marine benthic communities, occurring as an epiphyte or colonizing hard substrata, and has a worldwide distribution. The hyaline appearance of the valve and the high striation density, which is indiscernible under a light microscope, makes the identification of most species difficult and very few studies have investigated their morphology, phylogeny or ecology in detail. In an extensive study of diatom communities from the hypersaline Mar Menor coastal lagoon (SE Spain), several new taxa were found. Herein we propose Hyalosynedra lanceolata sp. nov. based on morphological observations (light and electron microscopy) and molecular data (phylogenetic and sequence divergence analyses). The species has distinctive morphological characters (radiate colony, biseriate striation, lanceolate sternum and two long laminar lobed chloroplasts) that are new for the genus and have been included in a proposal to extend the genus description. Our results also show that H. toxoneides does not belong to Hyalosynedra, but appears to be more closely related to Thalassionema and Thalassiothrix . However, further molecular and morphological research is needed to clarify its taxonomic position.